Association of three genetic loci with uric acid concentration and risk of gout: a genome-wide association study - Dehghan, Abbas (2008)
BACKGROUND: Hyperuricemia, a highly heritable trait, is a key risk factor for gout. We aimed to identify novel genes related to serum uric acid (UA) and gout. METHODS: Genome-wide association studies (GWAS) were conducted for serum UA in the Framingham Heart Study (FHS; n=7699) and the Rotterdam Study (RS; n=4148). Genome-wide significant SNPs were replicated among white (n=11024) and black (n=3843) Atherosclerosis Risk in Communities (ARIC) Study participants. The association of these SNPs was evaluated with gout; results in whites were combined using meta-analysis. RESULTS: Three loci in FHS and two in the RS showed genome-wide significance with UA. Top SNPs in each locus were: missense SNP rs16890979 in SLC2A9 (p=7.0×10(−168) [whites]; 2.9×10(−18) [blacks]), missense SNP rs2231142 in ABCG2 (p=2.5×10(−60) [whites]; 9.8×10(−4) [blacks]), and rs1165205 in SLC17A3 (p=3.3×10(−26) [whites]; 0.33 [blacks]). All SNPs showed direction-consistent association with gout in whites: rs16890979 (OR 0.58 per T allele, 95% CI 0.53–0.63, p=1.2×10(−31)), rs2231142 (OR=1.74 per T allele, 1.51–1.99, p=3.3×10(−15)), and rs1165205 (OR=0.85 per T allele, 0.77–0.94, p=0.002). In ARIC blacks, rs2231142 showed a direction-consistent association with gout (OR=1.71, 1.06–2.77, p=0.028). An additive genetic risk score (0–6) comprised of high risk alleles at the three loci showed graded associations in each study across scores with UA (from 272–351 μmol/l [FHS], 269–386 μmol/l [RS], and 303–426 μmol/l [ARIC whites]) and gout (prevalence 2–13% [FHS], 2–8% [RS], 1–18% [ARIC whites]). CONCLUSIONS: We identified three genetic loci (two novel including a candidate functional variant Q141K in ABCG2) related to UA and gout. A score based on genes with a putative role in renal urate handling showed a substantial risk gradient for gout.